Isolation and screening of biosurfactant-producing marine bacteria from Kuantan Port, Pahang, Malaysia - Ismail, Muhammad Isminhaziq; Azizan, Nur Hafizah; Mohd Ashaari, Mardiana (Zibeline International Publishing Sdn. Bhd., 2018)
Biosurfactants play an important role in bioremediation of organic pollutants such as petroleum hydrocarbon. The unique properties of biosurfactants make them possible to be used in the remediation of hydrocarbon contaminated sites. Therefore, the existence of indigenous microorganisms that have the ability to consume petroleum hydrocarbon as carbon source and simultaneously produce biosurfactants in order to facilitate the hydrocarbon metabolism can be manipulated for bioremediation purposes. In this study, isolation and screening of potential biosurfactant-producing bacteria from two sampling points in Kuantan Port seawater were successfully done. Amongst the isolates, 4 out of 7 isolates from Point A were Gram negative bacteria and 2 out 5 isolates from Point B were Gram negative bacteria. The positive oxidase test resulted for all isolates from Point A and only B5 from Point B produced negative result. Catalase test conducted produced positive results on isolates from Point A (A3, A5, A6& A7) and Point B (B1, B2, B4 & B5).The highest percentage emulsification index measured belonged to isolate B4 and B5 which are 67%, thus make these isolates to be the most promising biosurfactant producers. Further identification by 16S rRNA gene found that isolates were closely related to Rhodococcus erythropolis (A1), Psedomonas stutzeri (A2), Pseudoalteromonas lipolytica (A3, A6 and B4), Vibrio brasiliensis (A4 and B2), Vibrio tubiashii (B1), Marinobacter salsuginis (A5), Labrenzia aggregate (A7), Marinococcus halophilus (B3) and Thalassospira xianmenensis(B5). Hence, through biosurfactant activities exhibited by isolates, B4 and B5 were the most potential isolates to produce biosurfactant. Therefore, these isolates can potentially be exploited to aid in bioremediation of petroleum hydrocarbon contaminated sites and would also be useful to enhance oil recovery in petroleum industry.